2023
DOI: 10.3389/fphar.2023.1124297
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing medication adherence in multi-ethnic Asian patients with chronic diseases in Singapore: A qualitative study

Abstract: Background: Poor medication adherence can lead to adverse health outcomes and increased healthcare costs. Although reasons for medication adherence have been widely studied, less is explored about factors affecting medication adherence for patients in non-Western healthcare setting and from Asian cultures. This study aimed to explore cultural perspectives on factors influencing medication adherence among patients with chronic diseases in a multi-ethnic Asian healthcare setting.Methods: We conducted a qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 55 publications
(64 reference statements)
2
15
0
Order By: Relevance
“…Therefore, it is proposed that a fifth role, that of individuals as “partners in care” be considered in self‐management, to promote collaborative goal‐setting and shared decision‐making (Duprez et al, 2020) in the Asian context. Our findings are consistent with earlier qualitative studies with Asian individuals which suggests that individuals' voices should be included when developing a self‐management plan that considers their cultural practices and preferences to achieve greater adherence (Kumar et al, 2016; Yoon et al, 2023).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, it is proposed that a fifth role, that of individuals as “partners in care” be considered in self‐management, to promote collaborative goal‐setting and shared decision‐making (Duprez et al, 2020) in the Asian context. Our findings are consistent with earlier qualitative studies with Asian individuals which suggests that individuals' voices should be included when developing a self‐management plan that considers their cultural practices and preferences to achieve greater adherence (Kumar et al, 2016; Yoon et al, 2023).…”
Section: Discussionsupporting
confidence: 91%
“…However, there is a need for absolute trust in individuals' capability to partner in their own self‐management‐related decisions. Thus, motivating individuals by including their voices and promoting their ownership as equal partners is needed as suggested in studies from Asia (Kumar et al, 2016; Yoon et al, 2023) and Western countries (e.g., Duprez et al, 2020). The dominant position of HCPs and families of individuals in the current Asian healthcare system might hinder the inclusion of individuals as partners.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to patient-related factors, healthcare providers should also focus on healthcare system-related factors that affect medication adherence [15][16][17][18]. For example, the availability and affordability of medications, the accessibility of healthcare facilities, and the quality of healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…Patients also reported uncertainties about the efficacy of statins, scepticism about overprescribing and mistaken perceptions that statins are indicated only for patients with serious health conditions 10. Additionally, medication adherence is also influenced by cultural beliefs such as the notion of modern medicines as harms and fatalistic orientations towards escalation of doses and polypharmacy 26. Previous studies have shown that patients with negative medication beliefs were more than twice as likely to be non-adherent as patients with positive beliefs, and those with greater concerns regarding medication were significantly less likely to adhere 27 28.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these beliefs about medicines have been shown to be potentially modifiable by patient education and counselling 29. Some strategies that could be employed include using familiar language for patient education, patient empowerment on the benefits of medication optimisation and combining individual risk assessment using computer programmes with a shared decision-making process 26 30…”
Section: Discussionmentioning
confidence: 99%